Contributions from workers' health to the child education: workers' psychological suffering in a day-care center in the city of São Paulo (Cadernos de Psicologia Social do Trabalho, 2007)
This intervention-research, which started during a period of supervised training, was developed during the year of 2006. It began with the observation of the increasing number of complaints by child development assistants from day-care centers associated to the city of São Paulo who have been turning to the reference center for workers' health as well as to their trade union with grievances regarding psychological suffering related to work. This research aimed not only to contribute with the women workers of one of the associated day-care centers in the inquiry of the causes of this mental suffering they have gone through but also to collaborate with the construction of transforming forms of confronting such reality by the collectively produced connection between practical knowledge (the workers' know-how) and theoretical knowledge (the one we bring because of our insertion in the university) of the involved sides. For that, periodic meetings with the workers in the day-care center, observation of their daily routine, meetings with the leading team of the institution were carried out and then fed back to all the participants. The work disclosed the presence of intense psychological suffering and humiliation experiences related to their work, features recently acquired in the current public policy directed to Child Education in Brazil.